Atypical Association of Angelman Syndrome and Klinefelter Syndrome in a Boy with 47,XXY Karyotype and Deletion 15q11.2-q13 - Javier Sánchez; Ana Peciña; Olga Alonso-Luengo; Antonio González-Meneses; Rocío Vázquez; Guillermo Antiñolo; Salud Borrego (Case Reports in Genetics)
Angelman syndrome (AS, OMIM 105830) is a neurogenetic disorder with firm clinical diagnostic guidelines, characterized by severe developmental delay and speech impairment, balanced and behavioral disturbance as well as microcephaly, seizures, and a characteristic electroencephalogram (EEG). The majority of AS cases (70%) are caused by a 15q11.2-q13 deletion on the maternally derived chromosome. The frequency of AS has been estimated to be between 1/10000 and 1/20000. Klinefelter syndrome (KS) occurs due to the presence of an extra X chromosome (karyotype 47,XXY). The main features in KS are small testes, hypergonadotropic hypogonadism, gynecomastia, learning difficulties, and infertility. We present what is, to our knowledge, the first case of a patient with both KS and AS due to a 15q11.2-q13 deletion on the maternally derived chromosome and an extra X chromosome of paternal origin. He showed dysmorphic features, axial hypotonia, and delayed acquisition of motor skills. Early diagnosis is essential for optimal treatment of AS children; this is one of the earliest diagnosed cases of AS probably due to the presence of two syndromes. Clinical findings in this patient here described may be helpful to identify any other cases and to evaluate recurrence risks in these families.